Occurence and residency patterns of humpback whales off Réunion Island during 2004–10 - Dulau-Drouot, Violaine; Fayan, Jacques; Mouysset, Laurent; Boucaud, Virginie (J. Cetacean Res. Manage., 2023)
Dedicated humpback whale surveys were conducted around Réunion Island during 2004–10. Boat-based surveys were conducted from June to October, in the main objective of collecting photo-identification data. For 2004–10, a total of 501 survey trips, representing 1,530 hours of onsearching effort, and 724 humpback whale sightings were achieved. Although effort had a significant influence on the number of sightings, sighting rate was shown to increase significantly from 2007 onwards, with a peak in 2008. Seasonal variations were observed, with significantly higher numbers of sightings occurring in July–September. Larger number of whales, together with increased survey effort, led to larger datasets collected in 2008–10, allowing further investigation of residency pattern. Within-year recaptures from fluke photographs showed that a relatively large proportion (30%) of the identified whales was recaptured on more than one day around the island. Maximum recapture interval reached 64 days, with a mean ranging 22–29 days for 2008–10. Mean residency, estimated from expected lagged identification rate, was 25 days. Mothers with a calf were shown to reside around the island for longer period of time than other individuals. A seasonal pattern of residency was demonstrated, with single capture individuals occurring early in the season, mainly as singleton or pairs, while individuals showing higher recapture interval were present around the island from August to October. Between-year recaptures were reported for 2009–10, with five individuals re-sighted on consecutive years. The fluke catalogue for Réunion includes 312 distinct individuals identified during 2004–10 surveys, together with 21 additional whales captured opportunistically since 2001. The increasing trend in the number of whales, the high residency time observed for 2008–10 and the recent occurrence of inter-annual recaptures suggest that Réunion Island has become an important migratory site for humpback whales within the south-western Indian Ocean (Breeding Stock C). The species might expand its spatial range by occupying new breeding sites (or re-occupying old ones) within the south-western Indian ocean, as a result of population growth.